Analysis of Student Mastery of Concept on Static Fluid Through the Guided Inquiry Flipped Classroom Model - Sofia Azhari; Lia Yuliati; Sentot Kusairi (Universitas Lambung Mangkurat, 2023)
This study aimed to analyze students' concept acquisition of static fluid material in the pressure sub-chapter through the Guided Inquiry Flipped Classroom (GIFC) model. This type of research is quantitative, using a one-group pretest-posttest research design. The research subjects consisted of 31 students of XI MIPA 4. The measurement instrument in this study was a concept acquisition test, which consisted of 3 essay questions. Two supervisors have guided the instruments used, and they are valid. The data analysis technique uses paired t-test analysis and effect size analysis. The results of this study indicate significant differences between the pretest and posttest by the results of the paired t-test analysis and that guided inquiry affects concept acquisition. This study implies that this guided inquiry flipped classroom effectively improves students' concept acquisition. The results of this study can be used as input for educators to use the GIFC model to improve students' concept acquisition.